Analysis Of Factors Affecting Consumer Satisfaction and Loyalty Toward Bulog Rice In Mojokerto Regency - Armana, Andru; Soedarto, Teguh; Atasa, Dita (Kadiri University - Faculty of Agriculture, 2026)
This study aims to analyze the influence of product quality, price, agent service, sales location, and brand image on consumer satisfaction and loyalty toward BULOG rice in Mojokerto. Using a quantitative approach with 100 respondents selected through purposive sampling, data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) in SmartPLS. The results indicate that while product quality, agent service, and sales location significantly influence satisfaction, they function as